New contributions to the understanding of Kiruna-type iron oxide-apatite deposits revealed by magnetite ore and gangue mineral geochemistry at the El Romeral deposit, Chile - Rojas, P.A.; Barra, F.; Deditius, A.; Reich, M.; Simon, A.; Roberts, M.; Rojo, M. (Elsevier BV, 2018)
Iron oxide-apatite (IOA) or Kiruna-type deposits are an important source of iron and other elements including REE, U, Ag, and Co. The genesis of these deposits remains controversial, with models that range from a purely magmatic origin to others that involve variable degrees of hydrothermal fluid involvement. To elucidate the formation processes of this deposit type, we focused on the Chilean Iron Belt of Cretaceous age and performed geochemical analyses on samples from El Romeral, one of the largest IOA deposits in northern Chile. We present a comprehensive field emission electron microprobe analysis (FE-EMPA) dataset of magnetite, apatite, actinolite, pyroxene, biotite, pyrite, and chalcopyrite, obtained from representative drill core samples. Two different types of magnetite grains constitute the massive magnetite bodies: an early inclusion-rich magnetite (Type I); and a pristine, inclusion-poor magnetite (Type II) that usually appears as an overgrowth around Type I magnetite. High V (∼2500-2800 ppm) and Ti concentrations (∼80-3000 ppm), and the presence of high-temperature silicate mineral inclusions (e.g., pargasite, ∼800-1020°C) determined by micro-Raman analysis indicate a magmatic origin for Type I magnetite. On the other hand, high V (2300-2700 ppm) and lower Ti (50-400 ppm) concentrations of pristine, inclusion-poor Type-II magnetite indicate a shift from magmatic to hydrothermal conditions for this mineralization event. Furthermore, the composition of primary actinolite (Ca- and Mg-rich cores) within Type-II magnetite, the presence of F-rich apatite and high Co:Ni ratios (>1-10) of late stage pyrite mineralization are consistent with a high temperature (up to 840°C) genesis for the deposit. At shallow depths of the deposit, the presence of pyrite with low Co:Ni ratios (<0.5) and OH-rich apatite which contains higher Cl concentrations relative to F record a dominance of lower temperature hydrothermal conditions (<600°C) and a lesser magmatic contribution. This vertical zonation, which correlates with the sub-vertical shape of the massive iron ore bodies, is concordant with a transition from magmatic to hydrothermal domains described in several IOA deposits along the Chilean Iron Belt, and supports a magmatic-hydrothermal model for the formation of the El Romeral. The close spatial and temporal association of the deposit with the Romeral Fault System suggests that a pressure drop related to changes in the tectonic stress had a significant impact on Fe solubility, triggering ore precipitation.